Analyzing Changes in Traditional Industries: Challenges and Opportunities in the E-commerce Era - Ganeva Ravi; Muhammad Farras Nur; Ade Kiswara (Pandawan Sejahtera Indonesia, 2023)
Technological progress has rapidly revolutionized the global business sphere, with e-commerce emerging as a pivotal force in transforming traditional industries. This study undertakes a detailed bibliometric examination utilizing VOSviewer software to delve into the ramifications of e-commerce on conventional sectors and its role in global economic metamorphosis. Through identifying predominant keywords, notable publications, and collaborative research networks, the analysis underscores primary research trajectories. Notably, technology, innovation, education, knowledge, and investment emerge as pillars in navigating digital evolution. Furthermore, burgeoning areas like digital commerce, the circular economy, and blockchain present prospects for extended research. This study enhances our comprehension of the intricate shift traditional sectors undergo amidst the e-commerce surge. These insights bear significance for policymakers, entrepreneurs, and scholars, shedding light on potential hurdles and exploitable avenues amid digital upheaval. Consequently, this paper serves as a rich resource for those keen on grasping and maneuvering the intricacies of digital transformation within established industrial landscapes.